Modeling, Design, and Development of Soft Pneumatic Actuators with Finite Element Method2 . Issue 6 (3rd December 2015) - Moseley, Philip; Florez, Juan Manuel; Sonar, Harshal Arun; Agarwal, Gunjan; Curtin, William; Paik, Jamie
Abstract : This work presents a comprehensive open‐source simulation and design tool for Soft pneumatic actuators (SPAs) using finite element method, compatible and extensible to a diverse range of soft materials and design parameters. Thorough characterization of the hyperelastic and viscoelastic behavior is illustrated using a sample soft material (Ecoflex 00_30), and an appropriate material constitutive law. SPA performance (displacement and blocked‐force) are simulated for two types of SPA and validated with experimental testing. Real‐world case studies are presented in which SPA designs are iteratively optimized through simulation to meet specified performance criteria and geometric constraints. Abstract : Soft pneumatic actuators (SPAs) are compliant, elastomer‐based actuators that enable safer human–robot interaction. This work presents an open‐source simulation and design tool for SPAs using finite element method, compatible and extensible to different soft materials and design parameters.